Opposing interests in the legalization of non-procedural forest conversion to oil palm in Central Kalimantan, Indonesia. (15th December 2016) - Setiawan, Eko N.; Maryudi, Ahmad; Purwanto, Ris H.; Lele, Gabriel
Abstract: Demand for forestland for non-forest uses, mostly oil palm, has increased dramatically in the past few years and has become a chief driver of deforestation in Central Kalimantan. In this paper, we aim to shed light on how multiple levels of government create a facilitating environment for oil palm expansion. In our research, we employed three different methods: content analysis of key policy documents, participant observations, and expert interviews. We found that the technical complexities of formal procedures for the conversion of forest to oil palm are relatively easy to bypass. Contradicting laws and regulations have created a situation where the Ministry of Environment and Forestry (MoEF) and local governments have relatively equal legal mandates and authority over land-use and allocation. This is further complicated by the ambiguity of the decentralization policy. Enabled by the spatial planning law and the decentralization laws, local governments have aggressively issued plantation licenses for forest areas without the formal release of the forest from the Ministry of Forestry. The issuance of plantation permits has also been legitimized by other policies within central government, which have made oil palm a national priority.